Associations with fracture in patients with diabetes: a nested case–control study. Issue 2 (12th February 2016) - Starup-Linde, Jakob; Gregersen, Søren; Vestergaard, Peter
Abstract : Objectives: Diabetes mellitus is associated with an increased risk of fractures, which is not fully explained by bone mineral density and common risk factors. The aim of this study is to investigate the association of medication and biochemical markers on the risk of fracture in a diabetes population. Design and setting: A nested case–control study was conducted based on Danish diabetes patients from The Danish National Hospital Discharge Registry. Participants: The cases of the study were diabetes patients with a fracture (n=24 349), and controls were diabetes patients with no fracture (n=132 349). A total of 2627 diabetes patients were available for an analysis of patient characteristics, comorbidities, biochemical parameters and drug usage. Results: Age (OR=1.02, 95% CI 1.01 to 1.04), diabetes duration (OR=1.06, 95% CI 1.02 to 1.09), a diagnosis of previous fracture (OR=2.20, 95% CI 1.55 to 3.11), an alcohol-related diagnosis (OR=2.94, 95% CI 1.76 to 4.91), total cholesterol level (OR=2.50, 95% CI 1.20 to 5.21) and the usage of antiepileptics (OR=2.12, 95% CI 1.39 to 3.59) all increased the odds of fracture. Low-density lipoprotein cholesterol levels decreased the odds of fracture (OR =0.34, 95% CI 0.16 to 0.74), where the level of 3.04–5.96 mmol/L was optimal with regard to fracture risk. Conclusions: Low-density lipoprotein cholesterol may improve our understanding of fractures in diabetes patients, and it may be added to current fracture risk models in diabetes patients.